Cloning, expression and characterization of stearoyl-acp desaturase gene from Jessenia bataua Mart. var. bataua - Sharian, Muhamad Syafiq (2012)
Jessenia bataua is one of the exotic palms species planted mainly at the Malaysian Palm Oil Board research stations for assessment of yield and agronomic traits. J.bataua was introduced to Malaysia by the oil palm breeders in the eighties and it was brought from South America. J. bataua produces relatively low oil yield despite the high value of the oil which contains 78% of oleic acid and 13% of palmitic acid. The oil resembles the olive oil in taste and chemical composition which makes this crop an exciting prospects in meeting the needs of highly unsaturated oil. To date, little is known about the biology and particularly the fatty acid biosynthesis in J. bataua palm. Stearoyl-ACP desaturase (SAD) is an important fatty acid biosynthetic enzyme responsible for the production of oleic acid. It is a soluble enzyme in the plastid which introduces a cis double into saturated stearoyl-ACP (18:0-ACP) at the Δ9 position to produce monounsaturated oleoyl-ACP (18:1-ACP). It has an important housekeeping role for producing unsaturated fatty acids for membrane lipid biosynthesis. In oil accumulating tissues like anthers, seeds and mesocarp, it is involved in the developmentally regulated process of storage lipid biosynthesis. Oleic acid is an omega-nine fatty acid, and considered as one of the healthier sources of fat in the diet. In this study, the full-length of SAD cDNA namely JbSAD has been cloned and characterized from the mesocarp of J. bataua by RT-PCR and RACE techniques, respectively. The objectives of this study were; to isolate and characterize SAD cDNA from the mesocarp tissue of J. bataua and to express SAD recombinant cDNA of J. bataua in Escherichia coli system. The full-length of JbSAD cDNA clone is ≈ 1540 bp with 1182 bp open reading frame encoding for a 30-amino acid signal peptide and a 363-amino acid mature peptide. The predicted molecular mass and isoelectric point of JbSAD is ≈ 45.04 kDa and 5.91, respectively. The deduced amino acid sequence of the JbSAD shares approximately 81% sequence identity to SAD from the other plants, with the highest homology to that of oil palm (≈ 96%). JbSAD also contains an acyl-acyl carrier protein-desaturase (acyl-ACPdesaturase) conserved domain which is a mu-oxo-bridged diiron-carboxylate enzyme that belongs to a broad superfamily of ferritin-like proteins. Southern blot analysis using acyl-ACP-desat-specific probe revealed that the JbSAD is a multiple-copy genes. Functional studies were also performed by expressing the JbSAD as a Histagged cDNA fusion protein in E. coli. Upon induction by 1 mM IPTG and incubation at a different temperatures, JbSAD migrated as a ≈ 60 kDa protein on SDS-PAGE, in agreement with the predicted of 59.61 kDa molecular mass. Identification of protein band corresponds to His-tagged-JbSAD protein fusion (≈ 60 kDA) was achieved by using the Western blot experiment. The fatty acid composition of the transformed E. coli was identified by the Gas Chromatography. The result showed that there was an increased in the relative proportion of oleic acid (by ≈ 15%) by overexpressing JbSAD in E. coli. The data suggested that JbSAD c(by ≈ 15%) by overexpressing JbSAD in E. coli. The data suggested that JbSAD cDNA expressed in E .coli was in its active form.DNA expressed in E .coli was in its active form.